علاقة بعض عوامل البيئة الداخلية للمنظمة بامكانية تطوير المنتج وتاثيرها فيه : دراسة استطلاعية لآراء المدراء في مصانع الغزل ونسيج الموصل وبغداد - د. اكرم احمد الطويل; صفوان ياسين الراوي (PROSPECTIVE RESEARCHES, 2023)
The present study endeavours to determine the relation and influence of internal environment factors in the organization with the possibility of product development in textile and weaving factories of Mosul and Baghdad. The study includes the internal environment factors which are within the limits of the organization and which can have relation and influence on many variables. Because of the limitation of the study concerning relation and influence the researchers have tried to include these dimensions within a comprehensive framework. Generally speaking, this study will answer the following questions: 1. Is there an obvious conception with the director of the sample factories about the concept of internal environment and its factors? 2. Is there an obvious conception about the concept, the causes, and stages of product development? 3. Do managers of the studied factories have obvious conception about the relation and the influence of some internal environmental factors in developing the product? The study has come up with the following conclusions: - There is moral relations between the internal environmental factors of the factories studied in this research and the possibility of developing the product. - There is moral influence of the internal environmental factors of the studied factories and on the possibility of developing the product. Finally, some outstanding recommendations are given.